Gender Differences in the Impact of the COVID-19 Pandemic on Employment, Unpaid Work and Well-Being in the EU - Sanna Nivakoski; Massimiliano Mascherini (Intereconomics)
Abstract Unpaid work carried out inside the home has increased in the pandemic, and evidence points to women’s share in care responsibilities and domestic tasks remaining higher than those of men in the pandemic, continuing the gender divides of past decades.